IMPLEMENTATION OF MULTICULTURAL EDUCATION IN IMPROVING INDONESIAN CHARACTER TO STUDENTS AT SMAN 3 TUALANG - Dio Yoan Sabrina, - (2023)
SMAN 3 Tualang is one of the schools located in Perawang Village, Tualang District, Siak Regency, Riau Province. Students at this school have a high level of diversity, starting from the diversity of religions, ethnicity, race, language, customs, beliefs, culture, and others. However, there are still students who have not been able to accept and adapt to this diversity. Teacher competency is needed in knowing and understanding as well as designing and providing Multicultural Education to students. In this study the approach used was qualitative with a case study research method. The selection of informants was carried out using techniquespurposive sampling with a total of 13 key informants and 2 supporting informants. Researchers used data triangulation and source triangulation to test the validity of the data. The results of research using social learning theory and structural functionalism theory found that teachers' knowledge and understanding of multicultural education includes (1) teachers know and understand multicultural education and apply multicultural values in schools; (2) teachers do not know and do not understand Multicultural Education but apply multicultural values at school; (3) teachers do not know and do not understand Multicultural Education and do not apply multicultural values in schools. While the teacher's efforts in designing and providing Multicultural Education include (1) teachers are able to design and implement Multicultural Education in an integrated manner in subjects; (2) teachers are able to plan to apply Multicultural Education in a non-integrated manner in subjects; (3) teachers are unable to design and apply Multicultural Education either in an integrated or not integrated manner in subjects. While solutions to problems due to diversity issues can be minimized or even avoided with the dimensions of Multicultural Education namelyContent Integration, the Knowledge Construction Process, Equity Pedagogy, Prejudice Reduction, andan Empowering School Culture.